“LET’S DISCUSS”: PICTURE-BASED SMALL GROUP DISCUSSION AS A STRATEGY TO ENHANCE EFL STUDENTS’ SPEAKING SKILLS - Ade Prawitna; I Gde Putu Agus Pramerta; Ni Wayan Krismayani (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2026)
One of the most important skills in learning English is speaking, although many junior high school students still struggle with speaking, especially when it comes to fluency, pronunciation, and grammar. Students are frequently inactive and reluctant to participate in speaking activities due to low self-confidence, a limited vocabulary, and a fear of making mistakes. Through the use of Small Group Discussion with Pictures, this study sought to enhance the speaking abilities of ninth-grade students at SMP Negeri 8 Denpasar in the academic year 2025/2026. Classroom Action Research (CAR), which consists of preparation, action, observation, and reflection, was used in this study. 39 students served as the study's subjects. Speaking tests (pre-test, post-test I, and post-test II) and a questionnaire were used to gather the data. The results showed a significant improvement in students’ speaking skills. The students’ improvement was from 54.71 (pre-test) to 65.97 (post-test I) and 77.98 (post-test II). Furthermore, 87.18% of the students reached the passing grade at the end of the second cycle. The questionnaire results showed positive responses toward the implementation of the strategy, particularly in increasing confidence, motivation, and participation in speaking activities. Based on the findings, it can be concluded that Small Group Discussion with Pictures is an effective strategy to improve students’ speaking skills. It is recommended that EFL teachers implement the strategy as an alternative technique in teaching speaking skills.